A Review of Sharia Economic Law on Excavator Leasing in Oil Palm Plantations - Elian Nur Syafaat; Zaenal Abidin; Triyana Wulandari; Hairul Hapzi (Zabags Qu Publish, 2025)
This study examines the practice of excavator leasing within oil palm plantation operations at Pondok Modern Darussalam Gontor Campus 10 Jambi from the perspective of Sharia economic law. The study is motivated by the growing demand for heavy equipment in agrarian sectors, which necessitates leasing arrangements that align with the Islamic ijarah contract. The primary objectives are to describe on-site excavator leasing practices and to evaluate their conformity with Islamic legal principles particularly regarding usufruct (benefit), clarity of compensation, rental duration, and maintenance responsibility. A qualitative field research design was employed, using in-depth interviews, participant observation, and document review involving operators, lessees, and equipment managers. Findings indicate that current practices generally adhere to core ijarah principles: agreements are entered into voluntarily, payments commonly include a fair down payment, and active on-site supervision supports contractual transparency. No explicit indications of riba, severe gharar, or systematic injustice were observed. The study contributes theoretically by extending contemporary ijarah applications to heavy-equipment leasing in agrarian contexts and offers practical guidance for drafting Sharia-compliant leasing contracts to enhance operational efficiency and legal conformity in plantation management.